In-situ preparation of Cu-BiOCl/Bi2O3-C-dots composite and excellent performance for photocatalytic bisphenol A degradation. (April 2022) - Xiao, Bing; Xu, Minghao; Lu, Bin; Wang, Yun; Liu, Hui; Chen, Rufen
Abstract: Economical elimination of organic pollutants from waste water has be paid more attention owing to its environmental and ecological significance. In this study, an easily achievable process to in-situ fabricate copper and co-modified Z-scheme BiOCl/Bi2 O3 heterojunction was proposed. The study on the formation mechanism indicated that the introduction of copper ions is favorable for the formation of Bi-based catalyst with flaky morphology while the addition C-dots makes the nanosheets loosely be packed and intercrossed each other. The composite exhibited a high degradation efficiency for Bisphenol A (BPA) and 91% of BPA was removal within 35 min under xenon lamp irradiation. The excellent photocatalytic performance was attributed to the synergistic effect of the in-situ formation Z-scheme BiOCl/β-Bi2 O3 heterojunction, multiple charge transfer channels including Cu 2+ /Cu + and C-dots, and efficient charge separation. The electron paramagnetic resonance (EPR) analysis and quenching tests revealed that O2 − play a main role in degradation of BPA. Based on the experimental results, the photo-catalytic mechanism is proposed and the degradation path of BPA is revealed. Graphical abstract: Image 1 Highlights: A heterojunction Cu-BiOCl/Bi2 O3 -C-dots was in-situ fabricated at room temperature. The formation mechanism of Cu-BiOCl/Bi2 O3 -C-dots composite was revealed. The Cu-BiOCl/Bi2 O3 -C-dots composite exhibited high photocatalytic BPA degradation. A photodegradation mechanism of BPA over Cu-BiOCl/Bi2 O3 -C-dots was proposed.